The relationship between personal protective equipment (PPE) comfort and nurses' behavior in the inpatient areas of Merauke regional hospital - Mohamad Saljan; Evin Palupi Irianti; Natalin Allorerung; Erma Retnaningtyas (Institute of Accounting Research and Novation (IARN), 2026)
The use of PPE aims to protect health workers from invasion by pathogenic microbes. The use of Personal Protective Equipment (PPE) by nurses is still considered inadequate in its implementation and application. The application of PPE in nursing care is influenced by various factors. One such factor is nurses' behavior in using PPE. This study aims to determine the effect of comfort in using PPE on nurses' behavior in using PPE at Merauke Regional Hospital. This study used a cross-sectional research technique. The sampling method used was stratified random sampling. Based on this calculation, the required sample size was 103 respondents. The independent variable in this study was comfort in using PPE, and the dependent variable was behavior in using PPE. The Chi-square correlation test was used. The Chi-square test yielded a p-value of 0.04 (p<0.05). These results concluded that there was a significant effect between comfort in using PPE and nurses' behavior at Merauke Regional Hospital. The SPSS output showed a correlation coefficient of moderate or moderately strong.